Prunella vulgaris extract and rosmarinic acid suppress lipopolysaccharide-induced alteration in human gingival fibroblasts - Galandáková, Adéla; Rajnochová Svobodová, Alena; Šimánek, Vilím; Ulrichová, Jitka (Toxicology in vitro, 2009)
Periodontitis is a chronic disease associated with inflammation of the tooth-supporting tissues. The inflammation is initiated by a group of gram-negative anaerobic bacteria. These express a number of irritating factors including a lipopolysaccharide (LPS), which plays a key role in periodontal disease development. Plant extracts with anti-inflammatory and anti-microbial properties have been shown to inhibit bacterial plaque formation and thus prevent chronic gingivitis. In this study we tested effects of Prunella vulgaris L. extract (PVE; 5, 10, 25microg/ml) and its component rosmarinic acid (RA; 1microg/ml) on LPS-induced oxidative damage and inflammation in human gingival fibroblasts. PVE and RA reduced reactive oxygen species (ROS) production, intracellular glutathione (GSH) depletion as well as lipid peroxidation in LPS-treated cells. Treatment with PVE and RA also inhibited LPS-induced up-regulation of interleukin 1beta (IL-1beta), interleukin 6 (IL-6), tumor necrosis factor-alpha (TNF-alpha) and suppressed expression of inducible nitric oxide synthase (iNOS). The results indicate that PVE and RA are able to suppress LPS-induced biological changes in gingival fibroblasts. The effects of PVE and RA are presumably linked to their anti-inflammatory activities and thus use of PVE and RA may be relevant in modulating the inflammation process, including periodontal disease.
Keywords: financování organizované; Drug Antagonism; Antioxidants; lipopolysacharidy; glutathion; oxidační stres; Gingiva; Depsides; Glutathione; Fibroblasts; rostlinné extrakty; Oxidative Stress; gingiva; lidé; Reactive Oxygen Species; fibroblasty; cinnamáty; kultivované buňky; Lipopolysaccharides; Cinnamates; depsidy; Humans; Financing, Organized; Cells, Cultured; antioxidancia; Prunella; reaktivní formy kyslíku; Plant Extracts; Cell Survival; viabilita buněk; antagonismus léků